If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 8x + -10 = 0 Reorder the terms: -10 + 2x + 8x = 0 Combine like terms: 2x + 8x = 10x -10 + 10x = 0 Solving -10 + 10x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 10x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 10x = 0 + 10 10x = 0 + 10 Combine like terms: 0 + 10 = 10 10x = 10 Divide each side by '10'. x = 1 Simplifying x = 1
| Ln(x)=0.21 | | lnx=0.21 | | 17y-7=9+2y | | 6x^2+5x+24=0 | | 7z-3=8z-9 | | 4x-20x=11 | | 4=5(x-2) | | 1/3*x^3*y^3=9 | | x^3+4x^2+8x+2=0 | | x^3-4x^2+8x+2=0 | | x^3-4x^2-8x-1=0 | | x^3-4x^2-8x+2=0 | | 4x^2-25x+20=-6x+8 | | b-5/3=2 | | 0=5b-30 | | 10(s-5)=-99 | | 0=56-30 | | z-6/9=7 | | x-8/9=2 | | f(-x)=7x+5 | | 60=2l+2(5w) | | 2(2+3y)-6y=4 | | 5(4+0.5w)+7w=1 | | =-3y^2+2y | | 81=16r^4 | | S+-4=7.3 | | (3x-y)/3 | | 4.2x-86=2.7x+7 | | 4.7x+8.16=2.52 | | 4/9-y/4=7/36 | | h(x)=3x^2-2x | | 8x+7=0*(5x+9) |